Design, Synthesis, and Photovoltaic Characterization of a Small Molecular Acceptor with an Ultra‐Narrow Band Gap. Issue 11 (1st February 2017) - Yao, Huifeng; Cui, Yong; Yu, Runnan; Gao, Bowei; Zhang, Hao; Hou, Jianhui
Abstract: The design of narrow band gap (NBG) donors or acceptors and their application in organic solar cells (OSCs) are of great importance in the conversion of solar photons to electrons. Limited by the inevitable energy loss from the optical band gap of the photovoltaic material to the open‐circuit voltage of the OSC device, the improvement of the power conversion efficiency (PCE) of NBG‐based OSCs faces great challenges. A novel acceptor–donor–acceptor structured non‐fullerene acceptor is reported with an ultra‐narrow band gap of 1.24 eV, which was achieved by an enhanced intramolecular charge transfer (ICT) effect. In the OSC device, despite a low energy loss of 0.509 eV, an impressive short‐circuit current density of 25.3 mA cm −2 is still recorded, which is the highest value for all OSC devices. The high 10.9 % PCE of the NBG‐based OSC demonstrates that the design and application of ultra‐narrow materials have the potential to further improve the PCE of OSC devices. Abstract : Mind the gap : A non‐fullerene electron acceptor with an ultra‐narrow optical band gap of 1.24 eV was prepared. Despite a low energy loss of 0.509 eV, the organic solar cell (OSC) device demonstrated a high power conversion efficiency of 10.9 % with an impressive short‐circuit current density of 25.3 mA cm −2 .